Mengembangkan Aspek Motorik Halus Anak Menggunakan Model Project Based Learning, Metode Demonstrasi Dan Media Bahan Alam Pada Kelompok B Di Tk Islam Madinaturramlah Banjarmasin - Siska Oktasari; Novitawati, Novitawati (CV. ITTC INDONESIA, 2025)
The problem identified in this study is the low development of fine motor skills in Group B children, especially in pasting activities. This conditon is caused by a lack of activities that support fine motor skill development and the use of unappealing, less varied learning media in the classroom. The purpose of this research is to of describe teacher activities, analyze children’s engagement, and assess the outcomes of children’s fine motor skill development. The study used a qualitative approach with a classroom action research design conducted over four meetings. The subjects consisted of 11 children from Group B at TK Islam Madinaturramlah Banjarmasin, including six boys and five girls. Data were analyzed descriptively using tables and charts to present the results clearly and systematically. The findings a showed that teacher activty reached the “Very Good” category, children’s participation increased from 9% in the first meeting to 100% by the fourth, and pasting skills improved from 0% to 100%. In conclusion, the application of Project-Based Learning, demonstration methods, and natural materials effectively enhanced children’s fine motor skills. These findngs can be useful reference for principals, teachers, future researchers to improve the quality of early childhood learning and classroom instructional practices in schools.